THE POSSE APPROACH: A PROMISING WAY to BOOST READING COMPREHENSION - Sepriana, Tanti; Hastini, Hastini; jamiluddin, Jamiluddin; Mertosono, Sudarkam R (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
The objective of this study was to examine whether the application of POSSE (predict, organize, search, summarize, evaluate) strategy could enhance the understanding of reading skills of tenth-grade pupils in SMAN 7 PALU. This study utilized designing quasi-experimental, dividing participants into an experiment group and a control group. The technique of purposive sampling was employed to decide the sample, comprising 36 students from the experimental group and 35 pupils from the control group. Gathering of data involved pre-test and post-test assessments, with analysis conducted utilizing paired sample t-tests with the support of SPSS v.29 for windows. The findings indicated that applying of the POSSE approach effectively enhanced the understanding of reading among tenth-grade students attending SMAN 7 PALU. This conclusion was substantiated by the results of conducting the paired sample t-test, which showed a statistically notable disparity (2-tailed=0.0010.05) in the students’ learning outcomes between the initial assessment and subsequent assessment.